Assessment of Mathematics Proof Construction: Preservice Mathematics Teacher Training and Upper Secondary School Students - Mohamad Waluyo; S Sutama; Nining Setyaningsih (Universitas Muhammadiyah Surakarta, 2025)
Constructing valid mathematical proofs is a fundamental yet persistent challenge for students. This study investigates the developmental trajectory of proof construction abilities among Indonesian students, spanning from upper secondary school (Grades 10-11) to undergraduate mathematics levels. Adopting a descriptive cross-sectional design, data were collected from 479 participants using open-ended proof construction tasks and a survey on proof perception. The results reveal a pervasive dominance of empirical proof schemes, where students rely on specific numerical examples rather than generalized logical arguments. Notably, formal proof construction was virtually non-existent at the secondary level, highlighting a significant pedagogical gap. While the frequency of formal proof attempts increased among university students, valid execution remained limited, indicating a disconnect between students' strategic knowledge and their normative understanding of